As contribuições da orientação empreendedora na internacionalização: um estudo de caso no miolo wine group - Lindemam, André Carvalho (Universidade do Vale do Rio dos Sinos, 2010)
By applying the concept of entrepreneurship to the organization comes to entrepreneurial orientation (EO), which refers to the entrepreneurial process, at the organizational level. The entrepreneurial orientation refers to the methods, practices and styles of decision making used to act in an entrepreneurial way. One way to realize the OE of an organization is through its dimensions: innovation, risk propensity and proactivity. Companies interested in operating in international markets, need creativity, proactivity and risk calculation, to help them to overcome the difficulties imposed by the market. Regarding operations in the international market, Brazilian companies are considered late for its inclusion in comparison to its competitors from developed nations. International operations requires determination of strategies that could allow the inflow of products, technologies, management, human resources and other resources of a company in a foreign country. It also involves choosing the best strategy, whether for export or investment contract and requires the company, appropriate actions to overcome barriers to internationalization, both for entry and / or operations. This research is qualitative in nature and examines, through a single case study, how entrepreneurship at the organizational level, here specified as entrepreneurial orientation (EO) through its dimensions, which are: innovation, risk propensity and proactivity, and their constituent elements, contribute in the context of internationalization of Brazilian wine group, represented by Inside Wine Group. Data were collected through in-depth interviews and documentary analysis. The main findings highlight the OE helps in the process of internationalization of the MWG through: strategic market entry, reducing the barrier of lack of association between Brazil and wine quality, to differentiate their products in relation to other Brazilian products in international competition, advanced technology, product quality, in harnessing the potential of some unexplored regions, and international benchmarking, increasing the volume of sales, in identifying threats and overall planning, identification of innovation and by strengthening the brand.
Keywords: Empreendedorismo; Orientação empreendedora; Internacionalização; Estratégias de entrada e operações internacionais; Barreiras à internacionalização; Entrepreneurship; Entrepreneurial orientation; Iinternalization; Entry strategies and international operation; Barrier to internalization; ACCNPQ::Ciências Sociais Aplicadas::Administração